Physical properties (MSCL) of IODP Hole 386-M0091B - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Multi-Sensor Core Logger (MSCL) data (P-wave velocity, gamma ray attenuation (GRA) density, magnetic susceptibility, natural gamma radiation (NGR), noncontact resistivity (NCR)) from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). These data were obtained from whole round core sections by means of a Geotek MSCL during the offshore phase of the expedition. The offshore phase of expedition 386 took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan. As the aforementioned parameters are sensitive to temperature core sections were stored for at least 6 hours after arrival on deck before measurement to allow for temperature equilibration. The core physical properties were measured at predetermined optimal instrument-based spatial and temporal sampling intervals. GRA density, P-wave velocity, NCR, and magnetic susceptibility were measured every 2 cm, and NGR measurements were obtained every 10 cm. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023